Four new species and new records of Atopsyche Banks (Trichoptera: Hydrobiosidae) from Pantepui biogeographical region (Venezuela) - Zamora-Muñoz, Carmen; Derka, Tomáš; Múrria, Cesc (Zootaxa, 2017)
Four new species of the genus Atopsyche Banks (Hydrobiosidae) from Pantepui biogeographical region (Venezuela) are described and illustrated: Atopsyche (Atopsaura) inmae n. sp., Atopsyche (Atopsaura) cristinae n. sp., Atopsyche (Atopsaura) svitoki n. sp., and Atopsyche (Atopsaura) carmenae n. sp. Molecular analyses (cox1 sequences) allowed larva-adult associations and the morphological description of larvae of two of the new species (A. inmae and A. cristinae). A phylogenetic tree is performed to assess the molecular validity of the species, establish evolutionary relation among them and interpret historical biogeography of tepuis. Finally, two new distributional records for A. (Atopsaura) atahuallpa are included, which up to now was known only from the type locality.